Perencaan Strategis Sistem Dan Teknologi Informasi Pada PT. Qta Travelindo Jaya Surabaya - Sutanto, Alvin; Sudarmaningtyas, Pantjawati; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract:PT Qta Travelindo Jaya Surabaya is a travel agency company that has been supported by the application, but the application that is not met expectations, for the development of applications based only on immediate needs with different platforms. This resulted in no integration of data between parts, occurs redundancy of data, not optimal application usage, budget development of Information Systems and Information Technology (IS/IT) is not controlled, and the disjointed IS/IT with business objectives.In order to overcome the constraints mentioned above, it is necessary to Strategic Planning IS/IT. In drawing up the Strategic Planning IS/IT used method of Ward & Peppard so that IS/IT can be aligned with its business strategy. In this method the synchronization between the company's objectives with the aim of IS/IT. Besides Ward & Peppard method, there is a method of analysis or ancillary aspects, as follows: Strenghts, Weakness, Opportunities, and Threats (SWOT), Finance, Marketing, Operations, Human Resources, Industrial Markets, Competitors, Political Regulations, and McFarlan.The results of the Strategic Planning in the form of IT/IS document. This document contains the Application Portfolio namely Sales Information System (Invoice), Mobile Web Application Airlines plane and hotel, and webstite Gotravelindo. Documentation is made for three (3) years of the coming period and will be used as a recommendation IS/IT development be focused, IS/IT strategy aligned with business strategy, and can determine the competence of the resources needed in the IS/IT Qta Travelindo PT Jaya Surabaya